2021
DOI: 10.1016/j.hemonc.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the enrollment to systemic therapy and survival for patients with multiple myeloma

Abstract: Background Disparities driven by socioeconomic factors have been shown to impact outcomes for cancer patients. We sought to explore this relationship among patients with multiple myeloma (MM) who were not considered for hematopoietic stem cell transplant in the first-line setting and how it varied over time. Methods We queried the National Cancer Database for patients diagnosed with MM between 2004 and 2016 and included only those who received systemic therapy as the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…115,119,120 Indeed, Black people have benefited less from recent treatment advancements because of less access to care, including lower utilization of the most recent treatment advances and more delays in treatment. 115,121…”
Section: Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…115,119,120 Indeed, Black people have benefited less from recent treatment advancements because of less access to care, including lower utilization of the most recent treatment advances and more delays in treatment. 115,121…”
Section: Myelomamentioning
confidence: 99%
“…The somewhat higher contemporary survival among Black people may reflect a lower prevalence of aggressive disease subtypes 115,119,120 . Indeed, Black people have benefited less from recent treatment advancements because of less access to care, including lower utilization of the most recent treatment advances and more delays in treatment 115,121 …”
Section: Selected Cancer Sitesmentioning
confidence: 99%
“…Guillermo CL et al reported that male sex was one of predictive factors for early mortality of multiple myeloma patients (Guillermo CL et al 2007). Other studies also con rmed the association of female gender with improved survival (Jayakrishnan TT et al 2021;Ikeda T et al 2019). But in another study, female gender was con rmed to be associated with inferior overall survival (44.8 months vs. 49.9 months, P = 0.020) (Boyd KD et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…As such, we cannot fully determine how the staging and aggressiveness of disease differ between facilities, which may greatly impact survival differences. The lack of complete transplant data is a particularly large limitation, as this is an intervention that is generally unavailable at small community hospitals and is well established to benefit MM patients 9,35 . This may lead to significant selective pressure on facility selection for eligible patients.…”
Section: Discussionmentioning
confidence: 99%